2018
DOI: 10.15835/nsb10210260
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Yield and Proximate Composition of Aromatic Rice as Influenced by Inorganic and Organic Fertilizer Management

Abstract: Integrated use of organic and inorganic fertilizers can improve crop productivity and sustain soil health and fertility. To gain insights into the response of green manure and chemical fertilizer, the present study was conducted to evaluate the growth, yield and proximate composition of aromatic rice varieties in Aman season at the research farm of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh during the period from July to December 2014. The experiment was set up in split-plot design with three aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…BRRI dhan63 produced the highest dry matter hill -1 (15.39 g) followed by BRRI dhan50 (12.78 g) which was as good as Basmati (12.84 g) at 85 DAT (Figure 5). Similar results were reported by Sumon et al (2018) who reported that dry matter production hill -1 differed due to varietal characteristics.…”
Section: Total Dry Matter Production Hill -1supporting
confidence: 90%
“…BRRI dhan63 produced the highest dry matter hill -1 (15.39 g) followed by BRRI dhan50 (12.78 g) which was as good as Basmati (12.84 g) at 85 DAT (Figure 5). Similar results were reported by Sumon et al (2018) who reported that dry matter production hill -1 differed due to varietal characteristics.…”
Section: Total Dry Matter Production Hill -1supporting
confidence: 90%
“…It also escalates the differentiation process from the somatic to the reproductive phase, leading to higher grain and straw yield of aromatic rice. Sumon et al [ 42 ] and Sharma et al [ 43 ] also opined that INM involving FYM and green manuring is imminent for sustainably increasing rice yield. An increase in rice grain yield due to green manure incorporation might be attributed to the release of nutrients to soils slowly for a longer period after decomposition, resulting in better yield attributes.…”
Section: Discussionmentioning
confidence: 99%
“…Rice (Oryza sativa L.) is the most important cereal food crop which feeds the world's half of the population providing 35-60% of the total caloric requirements (Tayefe et al, 2014). In Bangladesh, rice is consumed as staple food since it is the main source of food and has incredible influence on its agrarian economy (Sumon et al, 2018;Paul et al, 2021). Approximately, 36.60 million tons of rice is produced from 11.42 million hectares of land in Bangladesh (BBS, 2020) of which Aus, Aman, and Boro rice covers 1.10, 5.56, and 4.76 million hectares of land with the production of 2.…”
Section: Introductionmentioning
confidence: 99%